Carbon Dioxide Absorption from Anæsthetic Atmospheres : (Section of Anæsthetics) - Waters, Ralph M. (1936)
A safe and practical technique for the application of carbon dioxide absorption from anæsthetic atmospheres is described. It has been found satisfactory in over 20,000 administrations over a period of fifteen years. High-grade soda lime is utilized as the chemical absorbent. Granules are placed in a canister between face mask, and breathing bag. The canister is carefully checked for efficiency by both chemical analyses and physical experiments. Its size, shape and arrangement is shown to be important for safety and maximum efficiency. Detailed techniques are described for the use of various agents. Advantages of carbon dioxide absorption are set forth. The “Apnœa” suggested by Guedel is described under the term “Controlled Respiration” and attention is called to certain of its advantages.